PEMBUATAN BIODIESEL DARI KELAPA DENGAN METODE KERING - Yesung Allo Padang; Mirmanto Mirmanto (Universitas Mataram, 2011)
Producing biodiesel by dry method has been conducted in the Laboratory of Energy Conversion, Mechanical Engineering Department, Mataram University. In the conventional method, coconut flesh is scrabbed and then squizzed to separate the coconut milk then from this milk obtained oil. In dry method, the flesh is cut in to small pieces then cook in the sealed container.Its vapor is collected , condensated and eventually oil is produced.By transesterification process biodiesel is obtained. The combination of metanol : coconut oil is varied as follow :10 (K0), 1:10 (K10), 2:10 (K20), dan 3:10 (K30). Biodiesel produced is then tested to evaluate its specific gravity,kinematic viscosity,flash point and calorifiec value.The result show that increased methanol concentration reduced specific gravity,kinematic viscosity,flash point and calorifiec value. Specific gravity for K0, K10, K20, and K30 in the transesterification process are 0.864, 0.851, 0.849, and 0.843, respectively. Kinematic viscosity for K0, K10, K20, and K30 are 5.65 mm2/s, 4.80 mm2/s, 4.29 mm2/s, and 3.52 mm2/s, respectively. Flash point for K0, K10, K20, and K30 are 62.330C, 58.670C, 54.670C, and 520C. Calorifiec value for K0, K10, K20, and K30 are 19601.842 Btu/lb, 19105.375 Btu/lb, 17803.337 Btu/lb, and 16548.844 Btu/lb.